Molecular detection of mixed infections with multiple dengue virus serotypes in suspected dengue samples in Tamaulipas, Mexico - Rocío Requena-Castro; Miguel Ángel Reyes-López; Rosa Eminé Rodríguez-Reyna; Prisco Palma-Nicolás; Virgilio Bocanegra-García (Memorias do Instituto Oswaldo Cruz)
This study aimed to detect dengue virus (DENV) serotypes in serum samples obtained in Matamoros Tamaulipas, Mexico, and to determine the concordance of conventional nested reverse transcriptase polymerase chain reaction (RT-PCR) and a serological test [enzyme-linked immunosorbent assay (ELISA NS1)]. Here, we detected mixed infections consisting of four serotypes of DENV. The most prevalent serotype was DENV-1, followed by DENV-4. This is the first report of DENV-4 in our region. Mixed infections were also detected in 21.5% of samples, and the predominant coinfection consisted of DENV-1 and DENV-2. Therefore, continuous epidemiological surveillance of DENV in this area is required to predict future forms of dengue heterologous infections and the effect of this on health care.